Design of a continuous emission monitoring system (CEMS) for the NH3 analyzer at PT. Pusri Palembang - Ivan Sofyan; Amrillah Nugrasyah (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2023)
PT. Pupuk Sriwidjaja Palembang (Pusri) is one of the urea fertilizer producers in Indonesia. Pusri is a fertilizer factory that received the Green PROPER award from the Ministry of the Environment in 2011 and 2012 and the Green Industry award from the President of the Republic of Indonesia in 2012. PT. Pusri demonstrated success in environmental management by achieving gold proper in 2022. Under the Minister of Environment Regulation (Permen LHK) No. 13 of 2021 concerning SISPEK (Continuous Industrial Monitoring Information System), which contains regulations regarding systems that aim to obtain emission data and information correctly, accurately, and continuously in an integrated manner. Data from monitoring stationary source emissions or stack emissions using continuous measurements or CEMS must be measured and evaluated. This study concerns the design of CEMS on the Induced Fan chimney in the Prilling Tower of the PIV Factory, which is designed to measure ammonia (NH3 Analyzer). The sampling probe has an automatic blowback function controlled automatically with Programmable Logic Control (PLC) or a simple relay. Blowback will use a water instrument with an available pressure of 4-7 kg/cm2. The NH3 (ammonia) measurement system is an extractive type. The NH3 component was measured using a laser beam and a power supply with specifications of 220 VAC, 50 Hz, and 1 phase with a measurement range of 0 ± 600 mg/NM3. PT. Pupuk Sriwidjaja Palembang (Pusri) adalah salah satu produsen pupuk urea di Indonesia. Pusri adalah pabrik pupuk yang mendapatkan penghargaan PROPER Hijau dari Kementrian Lingkungan Hidup tahun 2011 dan 2012, dan penghargaan Industri Hijau dari Presiden RI tahun 2012. PT. Pusri menunjukkan keberhasilan dalam pengelolaan lingkungan, dengan meraih proper emas pada tahun 2022. Sesuai dengan Peraturan Menteri Lingkungan Hidup (Permen LHK) No. 13 tahun 2021 tentang SISPEK (Sistem Informasi Pemantauan Industri secara Terus Menerus), yang berisi aturang mengenai sistem yang bertujuan untuk mendapatkan data dan informasi emisi secara benar, akurat, dan terus-menerus secara terintegrasi. Data hasil pemantauan emisi sumber tidak bergerak atau emisi cerobong dengan pengukuran secara terus menerus atau CEMS harus diukur dan dievaluasi. Studi ini mengenai perancangan CEMS pada cerobong Induced Fan di Prilling Tower Pabrik PIV yang dirancang untuk mengukur ammonia (NH3 Analyzer). Sampling probe memiliki fungsi automatic blow back yang dikontrol secara otomatis dengan Programable Logic Control (PLC) atau relay sederhana. Blow back akan menggunakan instrument air dengan tekanan yang tersedia 4-7 kg/cm2. Sistem pengukuran NH3 (ammoniak) termasuk jenis extractive. Pengukuran komponen NH3 menggunakan sinar laser, serta power supply dengan spesifikasi 220 VAC, 50 Hz, dan 1 phase dengan range pengukuran 0 ± 600 mg/NM3.